Study of role of laparoscopy in chronic abdomen (International Journal of Biomedical and Advance Research, 2015)
Study regarding role of laparoscopy in chronic abdomen was conducted at Shree Chhatrapati Shivaji Maharaj Sarvopachar Rugnalaya, Solapur during the period from March 2003 to November 2005. Patients of both sex and all age groups were included in the study. A total 30 patients were studied and results were as tabulated and analysed. In this study, 23 (76%) were females and remaining were (24%) were males. Most of the patients were in group 21-30 years (33%). Maximum female patients were in age group between 21-40 years. Out of 7 male patients, two patients were each in 12-20 years and 51 and above. 9 cases had appendicitis with finding as follows: long kinked appendix with periappendicular adhesions (4 patients), adherent to caecum(1), adherent to terminal ileum(1) and right iliac fossa and periappendicial adhesions (3). We conclude that females constituted maximum patients of chronic abdomen. Maximum age incidence of chronic abdomen was in 21- 30 years. In patients of chronic abdomen, there was poor co-relation between clinical diagnosis and laparoscopic findings. Maximum numbers of patients were in chronic appendicitis group. In this study, diagnostic laparoscopy was found relatively free of complications.